Pratiques de véridiction - Baudouin Dupret; Nicolas De Lavergne (Revue d'anthropologie des connaissances)
By a detailed analysis of gesture and language interactions, in the context of a Koranic school (kuttâb) of Upper‑Egypt, associating a master, the children who attend the courses and the other people present on the spot at the moment of the recording, this article aims at describing the unfolding of the teaching interaction which relates bodies, objects and words within a framework oriented towards the learning of the Koran. The norm there appears as a contextual practice, always renewed, contingent, but also constrained by the purposes from which it proceeds and to which the members of this specific setting are oriented, as by the materiality of various objects with which it must compose.